A platinum-based amorphous alloy porous catalyst for chlorine evolution reaction and preparation method thereof

Through the preparation of a porous catalyst of platinum-based amorphous alloy, the problem of low chlorine production efficiency in the chlorine-alkali industry is solved, the chlorine evolution reaction efficiency and stability are improved, the cost is reduced, and it is suitable for large-scale production.

CN115874216BActive Publication Date: 2024-12-20SHENZHEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211536570.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-02
Publication Date
2024-12-20
Estimated Expiration
2042-12-02

AI Technical Summary

Technical Problem

The existing chlor-alkali industry has high investment costs, low chlorine production efficiency and high consumption, resulting in high drinking water and wastewater treatment costs and environmental problems.

Method used

Using a platinum-based amorphous alloy porous catalyst, it is prepared by smelting, suction casting, hot pressing, acid solution treatment and electrodeposition of platinum, nickel, copper and phosphorus to form a platinum-based amorphous alloy porous with nanoscale ruthenium oxide. Catalysts are used to improve the efficiency of chlorine evolution reaction.

Benefits of technology

It improves the efficiency and stability of the chlorine evolution reaction, increases the chlorine generation volume, reduces production costs, and is simple in process and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115874216B_ABST
    Figure CN115874216B_ABST
Patent Text Reader

Abstract

The invention discloses a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction and a preparation method thereof. The preparation method comprises: platinum, nickel, copper and phosphorus are mixed and smelted in proportion to obtain a platinum-based amorphous alloy sheet; vacuum hot pressing is performed to embed nanometer-scale barium titanate particles into the surface of the platinum-based amorphous alloy sheet; then the sheet is immersed in an acidic solution to dissolve the barium titanate particles to obtain a platinum-based amorphous alloy substrate with a nanometer-scale porous structure; then electrodeposition is performed, wherein the electrolyte is a ruthenium chloride-potassium chloride mixed solution to obtain a platinum-based amorphous alloy porous substrate with nanometer-scale ruthenium loaded on the surface; then heat treatment is performed to obtain a finished product; the platinum-based amorphous alloy porous catalyst comprises a platinum-based amorphous alloy substrate with a nanometer-scale porous structure and nanometer-scale ruthenium oxide loaded on the surface of the platinum-based amorphous alloy substrate; the catalyst of the invention has high catalytic efficiency and long-term stability, improves the reaction efficiency of the chlorine evolution reaction, increases the amount of chlorine generated, and the preparation method is simple, low in cost, and suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts for water disinfection, and in particular to a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction and a preparation method thereof. Background Art

[0002] As the greatest public health achievement of the 20th century, water disinfection technology plays a vital role in reducing the incidence and death of infectious diseases caused by pathogenic microorganisms. Chlorine disinfection has become the most widely used disinfection method in the world due to its low cost, good disinfection effect and convenience. my country's drinking water hygiene standards stipulate that the free residual chlorine content of centralized water supply water shall not be less than 0.3 mg / L, and the water at the end of the pipe network shall not be less than 0.05 mg / L. In addition to being used for tap water treatment, chlorine can also effectively treat urban sewage in depth. As an important disinfectant, the social demand for chlorine has gradually increased. The preparation of chlorine comes from the chlor-alkali industry, which belongs to the traditional extensive development model and has the following problems: high investment cost, low chlorine gas production efficiency, high consumption, aggravated production costs, and caused many economic and environmental problems. Therefore, it is urgent to develop new efficient and stable catalysts for chlorine evolution reaction, improve the electrode chlorine evolution performance and stability, improve the efficiency of chlorine evolution reaction, improve the efficiency of chlorine gas production, reduce production costs, and provide new important material reserves and method selection for drinking water and wastewater treatment, and the preparation of disinfectants for public places. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction and a preparation method thereof in view of the defects of the prior art.

[0004] The technical solution adopted by the present invention to solve the technical problem is: to provide a method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction, comprising the following steps:

[0005] S1, mixing platinum, nickel, copper and phosphorus in proportion, smelting and suction casting, and cutting to obtain platinum-based amorphous alloy sheets;

[0006] S2, placing nano-scale barium titanate particles on the platinum-based amorphous alloy sheet, and hot pressing in a vacuum environment to embed the nano-scale barium titanate particles into the surface of the platinum-based amorphous alloy sheet, thereby obtaining a platinum-based amorphous alloy sheet with barium titanate particles on the surface;

[0007] S3, immersing the platinum-based amorphous alloy sheet with barium titanate particles on the surface in an acidic solution to dissolve the barium titanate particles embedded in the platinum-based amorphous alloy sheet to obtain a platinum-based amorphous alloy substrate with a nanoscale porous structure;

[0008] S4, electroplating a platinum-based amorphous alloy substrate having a nano-scale porous structure, wherein the electroplating electrolyte is a ruthenium chloride-potassium chloride mixed solution, to obtain a platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface;

[0009] S5. Heat-treating the platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface to obtain a platinum-based amorphous alloy porous catalyst with nano-scale ruthenium oxide loaded on the surface.

[0010] Furthermore, in step S1, the mass ratio of platinum, nickel, copper and phosphorus is 36:1:3:2, and the obtained platinum-based amorphous alloy sheet is Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 .

[0011] Furthermore, in step S1, a platinum-based amorphous alloy rod is obtained after suction casting, and is cut into platinum-based amorphous alloy discs, wherein the platinum-based amorphous alloy discs have a thickness of 750-800 μm and a diameter of 2-5 mm.

[0012] Furthermore, in step S2, the particle size of the nano-scale barium titanate particles is 30-200 nm, the hot pressing temperature is 190-205° C., the vacuum degree is 5-10 Pa, and the hot pressing pressure is 15-20 kN.

[0013] Furthermore, in step S3, the acidic solution is a 4-8 mol / L hydrochloric acid solution, and the reaction soaking time is 10-12 h.

[0014] Further, in step S4, the electrode system of the electrodeposition is a three-electrode system, the working electrode is a platinum-based amorphous alloy substrate with a nanoscale porous structure, the counter electrode is a platinum sheet, and the reference electrode is a silver chloride electrode. The electrodeposition voltage is -0.356 V relative to the standard hydrogen electrode, and the electrodeposition time is 500-800 s.

[0015] Further, in step S4, the concentration of ruthenium chloride in the ruthenium chloride-potassium chloride mixed solution is 0.1-0.5 mmol / L, and the concentration of potassium chloride in the ruthenium chloride-potassium chloride mixed solution is 0.05-0.15 mol / L.

[0016] Furthermore, in step S5, the heat treatment temperature is 420-450°C, and the heat treatment time is 150-180 min.

[0017] Furthermore, the particle size of the surface-loaded ruthenium oxide is 140-400 nm.

[0018] The present invention also provides a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction, which is obtained by the above-mentioned preparation method, comprising a platinum-based amorphous alloy substrate with a nano-scale porous structure and nano-scale ruthenium oxide supported on the surface of the platinum-based amorphous alloy substrate, wherein the platinum-based amorphous alloy substrate is Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 The pore size of the porous structure of the platinum-based amorphous alloy substrate is 30-200 nm, and the particle size of the nano-scale ruthenium oxide is 140-400 nm.

[0019] The beneficial effects of the present invention are as follows: a method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction is provided, which comprises the following steps: first preparing a platinum-based amorphous alloy, then embedding nanometer-sized barium titanate particles into the platinum-based amorphous alloy by hot pressing, and dissolving the barium titanate particles by a corresponding acidic solution, so that a nanometer-sized porous structure is formed on the surface of the platinum-based amorphous alloy, and electroplating and heat-treating the amorphous alloy substrate having the nanometer-sized porous structure so that the surface of the amorphous alloy is loaded with nanometer-sized ruthenium oxide, thereby forming a platinum-based amorphous alloy porous catalyst having the surface loaded with nanometer-sized ruthenium oxide; the platinum-based amorphous alloy porous catalyst of the present invention uses a platinum-based amorphous alloy as a substrate, which has thermoplasticity that ordinary metal materials do not have, is easy to form a nanometer-sized porous surface, and has strong stability; the porous structure on the platinum-based amorphous alloy substrate can greatly increase the specific surface area, realize more active sites to improve the efficiency of the chlorine evolution reaction; at the same time, the ruthenium oxide is nanometer-sized, has high catalytic efficiency and stable performance, has ultra-long stability, and can be stably used for 200 h or more, which improves the reaction efficiency of the chlorine evolution reaction and increases the amount of chlorine gas generated; the platinum-based amorphous alloy porous catalyst has simple process requirements, strong repeatability, low cost, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:

[0021] Figure 1 is a SEM image of a platinum-based amorphous alloy substrate having a nanoscale porous structure according to Example 1 of the present invention;

[0022] Figure 2 is a SEM image of a platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface in Example 1 of the present invention;

[0023] Figure 3 is an XRD diagram of a platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on its surface according to Example 1 of the present invention;

[0024] Figure 41 is an EDS image of a platinum-based amorphous alloy porous catalyst with nano-scale ruthenium oxide loaded on the surface according to Example 1 of the present invention, wherein the first image is an electron microscope image, the second image is an oxygen element distribution image, and the third image is a ruthenium element distribution image;

[0025] Figure 5 is an efficiency-voltage trend diagram of the platinum-based amorphous alloy porous catalyst of Example 3 of the present invention in a 3 mol / L NaCl solution for 900 seconds;

[0026] Figure 6 is a linear sweep voltammetric curve of the platinum-based amorphous alloy porous catalyst in Example 3 of the present invention in 3 mol / L NaCl solution and 3 mol / L NaNO3;

[0027] Figure 7 is an efficiency-voltage-time graph of the platinum-based amorphous alloy porous catalyst of Example 3 of the present invention in a 3 mol / L NaCl solution;

[0028] Figure 8 This is a comparative efficiency-voltage-time graph of a commercial ruthenium oxide catalyst in a 3 mol / L NaCl solution. DETAILED DESCRIPTION

[0029] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described in detail with reference to the accompanying drawings.

[0030] The present invention provides a method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction, comprising the following steps:

[0031] S1. Platinum, nickel, copper and phosphorus are mixed in proportion, smelted and suction-casted, and then cut to obtain platinum-based amorphous alloy sheets.

[0032] Furthermore, the mass ratio of platinum, nickel, copper and phosphorus is preferably 36:1:3:2, so that the alloy formed by smelting is Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 The alloy of this component can form an amorphous alloy, thus having thermoplasticity that ordinary metals do not have. Its good thermoplasticity makes it easy to form nanoporous surfaces, and at the same time, it has strong stability and is suitable as a substrate for porous catalysts.

[0033] Further, it is preferred that a rod-shaped platinum-based amorphous alloy is obtained after suction casting. The rod-shaped structure is easy to produce. According to the overall length of the platinum-based amorphous alloy rod and the selection of the predetermined thickness, the platinum-based amorphous alloy rod can be cut to form a plurality of platinum-based amorphous alloy discs, which can be polished with 600-2000 mesh sandpaper after cutting. The thickness of the platinum-based amorphous alloy disc includes but is not limited to 750-800 μm; the diameter is 2-5 mm. A diameter that is too large is not easy to produce and requires a very high cooling rate. The diameter of the platinum-based amorphous alloy disc is preferably 2-5 mm, and more preferably 5 mm.

[0034] The specific steps for preparing platinum-based amorphous alloy sheets are as follows: platinum, nickel, and copper are placed in the copper chamber of a WK series vacuum arc furnace at a mass ratio of 36:1:3, the mechanical pump is turned on, and the arc furnace is evacuated to 5 Pa or below. Under the premise of low vacuum, the molecular pump is turned on to evacuate the high vacuum to 3×10 -3 Pa, open the argon valve to pass an appropriate amount of argon, press the arc-starting switch, start the arc gun, and use 120 A current to burn the titanium ingot to absorb oxygen to ensure that there is no oxygen in the furnace. Aim the current at the copper cavity, adjust the arc current to 70-120 A, extinguish the arc gun after all the raw materials are melted, use a spoon to turn it over, start the arc gun again, repeat the subsequent steps, and repeat the melting three to five times to make the raw materials evenly fused together. The smelted master alloy containing platinum, nickel, and copper and the corresponding mass of phosphorus are loaded into the test tube (the mass ratio of platinum, nickel, copper and phosphorus is 36:1:3:2), and the Hefei Paquin station sealing machine is used to seal the tube, with an inclination angle of 15 degrees and a speed of 10 rpm. Turn on the mechanical pump to draw a low vacuum to below 5 Pa, and use the Hefei Compain water-fuel hydrogen-oxygen machine to seal the test tube at a flow rate of 200-300 L / H. Use a vacuum quenching spray casting machine to perform electromagnetic induction melting on the sealed test tube, step on the pedal to adjust the current to 20 A until the sample is completely melted, and P (phosphorus) is evenly mixed with the master alloy. Replace the new test tube, add boron trioxide and the master alloy mixed with induction melting P (phosphorus), use a vacuum quenching spray casting machine for induction melting and purification, and finally put the master alloy that has been melted and purified with phosphorus into the copper cavity of the vacuum arc furnace for suction casting to obtain platinum-based amorphous alloy rods. The diameter and length of the platinum-based amorphous alloy rods can be determined according to the corresponding forming mold, such as a diameter of 5 mm, etc.

[0035] S2. Place a platinum-based amorphous alloy sheet in a mold, take nano-scale barium titanate particles and place them on top of the platinum-based amorphous alloy sheet, and perform hot pressing in a vacuum, high temperature and argon cooling environment to embed the nano-scale barium titanate particles into the surface of the platinum-based amorphous alloy sheet, thereby obtaining a platinum-based amorphous alloy sheet with barium titanate particles on the surface.

[0036] Furthermore, the particle size of the nano-scale barium titanate particles is 30-200 nm, preferably 30 nm; barium titanate has a nano-scale size, does not agglomerate, and is easily removed by reaction in an acidic solution. It is a very suitable particle material for forming a porous structure, so that the porous pore size finally formed on the platinum-based amorphous alloy sheet is 30-200 nm. The hot pressing temperature is 190-205 ° C, the hot pressing is kept for 15-30 seconds, the vacuum degree is 5-10 Pa, and the protective gas argon is introduced after vacuum. The hot pressing pressure is 15-20 kN. When the temperature is about 190 ° C, the platinum-based amorphous alloy sheet will gradually soften, and the nano-scale barium titanate particles will be embedded in the surface of the platinum-based amorphous alloy sheet under pressure. After the nano-scale barium titanate particles are dissolved, a nanoporous structure can be formed in situ.

[0037] In the mold cavity of the mold, it is preferred to evenly place nano-scale barium titanate particles above the platinum-based amorphous alloy sheet, and the amount of nano-scale barium titanate particles used is set corresponding to the surface of the platinum-based amorphous alloy sheet to fully cover the surface of the platinum-based amorphous alloy sheet; for example, a platinum-based amorphous alloy disc with a diameter of 5 mm is selected to ensure that the nano-scale barium titanate particles can completely cover the platinum-based amorphous alloy disc.

[0038] S3. Immerse the platinum-based amorphous alloy sheet with barium titanate particles on the surface in an acidic solution to completely dissolve the barium titanate particles embedded in the platinum-based amorphous alloy sheet to obtain a platinum-based amorphous alloy substrate with a nano-scale porous structure.

[0039] Furthermore, the acidic solution is a 4-8 mol / L hydrochloric acid solution, and the reaction immersion time is 10-12 h, so as to fully dissolve the nano-scale barium titanate particles; preferably, a 6 mol / L hydrochloric acid solution has a better effect of dissolving the barium titanate particles. Soaking in the hydrochloric acid solution allows the barium titanate particles to react with the hydrochloric acid solution, and will not react with the platinum-based amorphous alloy sheet.

[0040] The prepared platinum-based amorphous alloy substrate with a nano-scale porous structure includes a platinum-based amorphous alloy sheet and a porous structure formed on the platinum-based amorphous alloy sheet; the porous structure is formed after the platinum-based amorphous alloy is softened by heat, nano-scale barium titanate particles are pressed into the surface of the platinum-based amorphous alloy, and the nano-scale barium titanate particles are removed.

[0041] S4. Place a platinum-based amorphous alloy substrate with a nanoscale porous structure in a three-electrode system for electrodeposition. In the three-electrode system, the working electrode is a platinum-based amorphous alloy substrate with a nanoscale porous structure, the counter electrode is a platinum sheet, the reference electrode is a silver chloride electrode, and the electrolyte is a ruthenium chloride-potassium chloride mixture, to obtain a platinum-based amorphous alloy porous substrate with nanoscale ruthenium loaded on the surface.

[0042] Specifically, the concentration of ruthenium chloride in the ruthenium chloride-potassium chloride mixture is 0.1-0.5 mmol / L, and the concentration of potassium chloride in the ruthenium chloride-potassium chloride mixture is 0.05-0.15 mol / L. During electrodeposition, the electrodeposition voltage is -0.356V (VS SHE, specifically refers to the voltage relative to the standard hydrogen electrode), and the electrodeposition time is 500-800 s, so that the ruthenium in the electrolyte is uniformly deposited on the platinum-based amorphous alloy substrate, thereby obtaining a platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface.

[0043] S5. The platinum-based amorphous alloy porous substrate with nano-level ruthenium loaded on the surface is subjected to heat treatment, so that the nano-level ruthenium is oxidized at high temperature to form ruthenium oxide, and finally a platinum-based amorphous alloy porous catalyst with nano-level ruthenium oxide loaded on the surface is obtained. Specifically, the platinum-based amorphous alloy porous substrate with nano-level ruthenium loaded on the surface can be placed in an annealing furnace for heat treatment, and the sample tube equipped with the platinum-based amorphous alloy porous substrate with nano-level ruthenium loaded on the surface is sealed with a sealing plug; the heat treatment temperature is 420-450 ° C, and the heat treatment time is 150-180 min, so that the nano-level ruthenium is fully oxidized to form ruthenium oxide, and the particle size of the formed ruthenium oxide is 140-400 nm.

[0044] The present invention also provides a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction, which is obtained by the above-mentioned preparation method, and comprises a platinum-based amorphous alloy substrate with a nano-scale porous structure and nano-scale ruthenium oxide supported on the surface of the platinum-based amorphous alloy substrate, wherein the platinum-based amorphous alloy substrate is Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 The pore size of the porous structure of the platinum-based amorphous alloy substrate is 30-200 nm, and the particle size of nano-scale ruthenium oxide is 140-400 nm.

[0045] The present invention provides a method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction, which comprises the following steps: first preparing a platinum-based amorphous alloy, then embedding nanometer-scale barium titanate particles into the platinum-based amorphous alloy by hot pressing, dissolving the barium titanate particles by a corresponding acidic solution, so that a nanometer-scale porous structure is formed on the surface of the platinum-based amorphous alloy, and performing electrodeposition and heat treatment on an amorphous alloy substrate sample having a nanometer-scale porous structure so that nanometer-scale ruthenium oxide is loaded on its surface, thereby forming a platinum-based amorphous alloy porous catalyst with nanometer-scale ruthenium oxide loaded on its surface; the platinum-based amorphous alloy of the present invention is The gold porous catalyst uses a platinum-based amorphous alloy as the substrate, which has thermoplasticity that ordinary metal materials do not have, is easy to form a nanoporous surface, and has strong stability; the porous structure on the platinum-based amorphous alloy substrate can greatly increase the specific surface area and realize more active sites to improve the efficiency of the chlorine evolution reaction; at the same time, the electrodeposited ruthenium oxide is at the nanometer level, with high catalytic efficiency and stable performance, which improves the reaction efficiency of the chlorine evolution reaction and increases the amount of chlorine gas generated; the platinum-based amorphous alloy porous catalyst has simple process requirements, strong repeatability, low cost, and is suitable for large-scale production.

[0046] Example 1

[0047] A platinum-based amorphous alloy porous catalyst for chlorine evolution reaction, comprising a platinum-based amorphous alloy substrate with a nano-scale porous structure and nano-scale ruthenium oxide loaded on the surface of the platinum-based amorphous alloy substrate, wherein the platinum-based amorphous alloy substrate is Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 The pore size of the porous structure of the platinum-based amorphous alloy substrate is about 30 nm, and the particle size of nano-scale ruthenium oxide is about 140 nm.

[0048] The specific preparation method comprises the following steps:

[0049] S1. Place platinum, nickel and copper in the copper chamber of a WK series vacuum arc furnace at a mass ratio of 36:1:3. Turn on the mechanical pump to evacuate the furnace to 5 Pa or below. Under low vacuum conditions, turn on the molecular pump to evacuate to a high vacuum of 3×10 -3Pa, open the argon valve to pass an appropriate amount of argon, press the arc-starting switch, start the arc gun, and use a 120 A current to burn the titanium ingot to absorb oxygen to ensure that there is no oxygen in the furnace. Aim the current at the copper cavity, adjust the arc current to 70 A, extinguish the arc gun after all the raw materials are melted, use a spoon to turn it over, start the arc gun again, repeat the subsequent steps, and repeat the melting three to five times to make the raw materials evenly fused together. The smelted master alloy containing platinum, nickel, and copper and the corresponding mass of phosphorus are loaded into the test tube (the mass ratio of platinum, nickel, copper and phosphorus is 36:1:3:2), and the Hefei Paquin station sealing machine is used to seal the tube, with an inclination angle of 15 degrees and a speed of 10 rpm. Turn on the mechanical pump to draw a low vacuum to below 5 Pa, and use the Hefei Compain water-fuel hydrogen-oxygen machine to seal the test tube at a flow rate of 200 L / H. Use a vacuum quenching spray casting machine to perform electromagnetic induction melting on the sealed test tube, step on the pedal to adjust the current to 20 A until the sample is completely melted, and P (phosphorus) is evenly mixed with the master alloy. Replace the new test tube, add boron trioxide and induction melt the master alloy mixed with P (phosphorus), use a vacuum quenching spray casting machine for induction melting and purification, and finally put the master alloy that has been purified and integrated with phosphorus into the copper cavity of a vacuum arc furnace for suction casting to obtain a platinum-based amorphous alloy rod (component Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 ), and cut into platinum-based amorphous alloy discs with a thickness of 750 μm and a diameter of 2 mm.

[0050] S2. Place the platinum-based amorphous alloy disc in a mold, take nano-scale barium titanate particles (particle size of about 30 nm) and place them on top of the platinum-based amorphous alloy disc, and perform hot pressing in a vacuum, high temperature and argon cooling environment for 30 seconds. The hot pressing temperature is 190 ° C, the vacuum degree is 5 Pa, and the hot pressing pressure is 15 kN, so that the nano-scale barium titanate particles are embedded in the surface of the platinum-based amorphous alloy disc to obtain a platinum-based amorphous alloy sheet with barium titanate particles on the surface.

[0051] S3, immersing the platinum-based amorphous alloy sheet with barium titanate particles on the surface in a 4 mol / L hydrochloric acid solution 5 for 12 h, dissolving the barium titanate particles embedded in the platinum-based amorphous alloy sheet, and obtaining a platinum-based amorphous alloy substrate with a nano-scale porous structure. The composition of the platinum-based amorphous alloy substrate with a nano-scale porous structure is Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 , which has the same structure as the platinum-based amorphous alloy sheet with barium titanate particles on the surface. The platinum-based amorphous alloy substrate with a nano-scale porous structure includes a platinum-based amorphous alloy substrate and a porous structure formed on the platinum-based amorphous alloy substrate. The SEM image of the platinum-based amorphous alloy substrate with a nano-scale porous structure is shown in Figure 1As shown in the figure, it can be seen that the nanoporous structure exists on the surface of the platinum-based amorphous alloy. The nanoporous structure increases its specific surface area, thereby increasing the active area of ​​the reaction.

[0052] S4. Place a platinum-based amorphous alloy substrate with a nano-scale porous structure in a three-electrode system for electrodeposition. In the three-electrode system, the working electrode is a platinum-based amorphous alloy substrate with a nano-scale porous structure, the counter electrode is a platinum sheet, the reference electrode is a silver chloride electrode, and the electrolyte is a ruthenium chloride-potassium chloride mixture. The concentration of ruthenium chloride in the ruthenium chloride-potassium chloride mixture is 0.1 mmol / L, and the concentration of potassium chloride in the ruthenium chloride-potassium chloride mixture is 0.05 mol / L. The electrodeposition voltage is -0.356 V (relative to the voltage of the standard hydrogen electrode), and the electrodeposition time is 500 s. A platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface is obtained. The SEM image of the platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface is shown in Figure 2. Figure 2 As shown in the figure, it can be seen that nano-scale ruthenium has been successfully deposited on the surface of the platinum-based amorphous alloy substrate with a nano-scale porous structure. The XRD pattern of the platinum-based amorphous alloy porous substrate with nano-scale ruthenium on the surface is shown in Figure 3 As shown by Figure 3 It can be seen that the X-ray diffraction pattern after electrodeposition is compared with the diffraction peak of standard Ru (ruthenium) in the database, which also proves that metallic ruthenium is successfully deposited on the surface of the platinum-based amorphous alloy substrate with a nanoscale porous structure.

[0053] S5. Place the platinum-based amorphous alloy porous substrate with nano-scale ruthenium on the surface into an annealing furnace for heat treatment, seal it with a sealing plug, and heat treat at a temperature of 420 °C for 180 min to obtain a platinum-based amorphous alloy porous catalyst with nano-scale ruthenium oxide on the surface. The EDS image of the platinum-based amorphous alloy porous catalyst with nano-scale ruthenium oxide on the surface is shown in Figure 1. Figure 4 As shown, the first picture is an electron microscope picture, the second picture is an oxygen element distribution picture, and the third picture is a ruthenium element distribution picture. It can be seen from the pictures that the distribution of ruthenium and oxygen elements basically overlap, proving that nanoscale metallic ruthenium has been successfully oxidized into nanoscale ruthenium oxide.

[0054] Example 2

[0055] A platinum-based amorphous alloy porous catalyst for chlorine evolution reaction, comprising a platinum-based amorphous alloy substrate with a nano-scale porous structure and nano-scale ruthenium oxide loaded on the surface of the platinum-based amorphous alloy substrate, wherein the platinum-based amorphous alloy substrate is Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 The pore size of the porous structure of the platinum-based amorphous alloy substrate is 100 nm, and the particle size of nano-scale ruthenium oxide is 250 nm.

[0056] The specific preparation method comprises the following steps:

[0057] S1. Place platinum, nickel and copper in the copper chamber of a WK series vacuum arc furnace at a mass ratio of 36:1:3. Turn on the mechanical pump to evacuate the furnace to 5 Pa or below. Under low vacuum conditions, turn on the molecular pump to evacuate to a high vacuum of 3×10 -3 Pa, open the argon valve to pass an appropriate amount of argon, press the arc-starting switch, start the arc gun, and use a 120 A current to burn the titanium ingot to absorb oxygen to ensure that there is no oxygen in the furnace. Aim the current at the copper cavity, adjust the arc current to 100 A, extinguish the arc gun after all the raw materials are melted, use a spoon to turn it over, start the arc gun again, repeat the subsequent steps, and repeat the melting three to five times to make the raw materials evenly fused together. The smelted master alloy containing platinum, nickel, and copper and the corresponding mass of phosphorus are loaded into the test tube (the mass ratio of platinum, nickel, copper and phosphorus is 36:1:3:2), and the Hefei Paquin station sealing machine is used to seal the tube, with an inclination angle of 15 degrees and a speed of 10 rpm. Turn on the mechanical pump to draw a low vacuum to below 5 Pa, and use the Hefei Compain water-fuel hydrogen-oxygen machine to seal the test tube at a flow rate of 250 L / H. Use a vacuum quenching spray casting machine to perform electromagnetic induction melting on the sealed test tube, step on the pedal to adjust the current to 20 A until the sample is completely melted, and P (phosphorus) is evenly mixed with the master alloy. Replace the new test tube, add boron trioxide and induction melt the master alloy mixed with P (phosphorus), use a vacuum quenching spray casting machine for induction melting and purification, and finally put the master alloy that has been purified and integrated with phosphorus into the copper cavity of a vacuum arc furnace for suction casting to obtain a platinum-based amorphous alloy rod (component Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 ), and cut into platinum-based amorphous alloy discs with a thickness of 780 μm and a diameter of 3 mm.

[0058] S2. Place a platinum-based amorphous alloy disc in a mold, take nano-scale barium titanate particles (particle size of about 110 nm) and place them on top of the platinum-based amorphous alloy sheet, and perform hot pressing in a vacuum environment at a temperature of 195 °C, a vacuum degree of 7 Pa, and a hot pressing pressure of 18 kN to obtain a platinum-based amorphous alloy sheet with barium titanate particles on the surface.

[0059] S3, immersing the platinum-based amorphous alloy sheet with barium titanate particles on the surface in a 6 mol / L hydrochloric acid solution for 11 h, completely dissolving the barium titanate particles embedded in the platinum-based amorphous alloy sheet, and obtaining a platinum-based amorphous alloy substrate with a nano-scale porous structure;

[0060] S4. Placing a platinum-based amorphous alloy substrate with a nano-scale porous structure in a three-electrode system for electrodeposition, wherein the working electrode is a platinum-based amorphous alloy substrate with a nano-scale porous structure, the counter electrode is a platinum sheet, the reference electrode is a silver chloride electrode, the electrolyte is a ruthenium chloride-potassium chloride mixture, the concentration of ruthenium chloride in the ruthenium chloride-potassium chloride mixture is 0.3 mmol / L, the concentration of potassium chloride in the ruthenium chloride-potassium chloride mixture is 0.1 mol / L, the electrodeposition voltage is -0.356 V (relative to the voltage of a standard hydrogen electrode), and the electrodeposition time is 600 s, to obtain a platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface;

[0061] S5. The platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface is subjected to heat treatment at a temperature of 430° C. for a heat treatment time of 175 min to obtain a platinum-based amorphous alloy porous catalyst with nano-scale ruthenium oxide loaded on the surface.

[0062] Example 3

[0063] A platinum-based amorphous alloy porous catalyst for chlorine evolution reaction, comprising a platinum-based amorphous alloy substrate with a nano-scale porous structure and nano-scale ruthenium oxide loaded on the surface of the platinum-based amorphous alloy substrate, wherein the platinum-based amorphous alloy substrate is Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 The pore size of the porous structure of the platinum-based amorphous alloy substrate is 200 nm, and the particle size of nano-scale ruthenium oxide is 380 nm.

[0064] The specific preparation method comprises the following steps:

[0065] S1. Place platinum, nickel and copper in the copper chamber of a WK series vacuum arc furnace at a mass ratio of 36:1:3. Turn on the mechanical pump to evacuate the furnace to 5 Pa or below. Under low vacuum conditions, turn on the molecular pump to evacuate to a high vacuum of 3×10 -3Pa, open the argon valve to pass an appropriate amount of argon, press the arc-starting switch, start the arc gun, and use a 120 A current to burn the titanium ingot to absorb oxygen to ensure that there is no oxygen in the furnace. Aim the current at the copper cavity, adjust the arc current to 100 A, extinguish the arc gun after all the raw materials are melted, use a spoon to turn it over, start the arc gun again, repeat the subsequent steps, and repeat the melting three to five times to make the raw materials evenly fused together. The smelted master alloy containing platinum, nickel, and copper and the corresponding mass of phosphorus are loaded into the test tube (the mass ratio of platinum, nickel, copper and phosphorus is 36:1:3:2), and the Hefei Paquin station sealing machine is used to seal the tube, with an inclination angle of 15 degrees and a speed of 10 rpm. Turn on the mechanical pump to draw a low vacuum to below 5 Pa, and use the Hefei Compain water-fuel hydrogen-oxygen machine to seal the test tube at a flow rate of 250 L / H. Use a vacuum quenching spray casting machine to perform electromagnetic induction melting on the sealed test tube, step on the pedal to adjust the current to 20 A until the sample is completely melted, and P (phosphorus) is evenly mixed with the master alloy. Replace the new test tube, add boron trioxide and induction melt the master alloy mixed with P (phosphorus), use a vacuum quenching spray casting machine for induction melting and purification, and finally put the master alloy that has been purified and integrated with phosphorus into the copper cavity of a vacuum arc furnace for suction casting to obtain a platinum-based amorphous alloy rod (component Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 ), and cut into platinum-based amorphous alloy discs with a thickness of 800 μm and a diameter of 5 mm.

[0066] S2. Place a platinum-based amorphous alloy disc in a mold, take nano-scale barium titanate particles (particle size of about 200 nm) and place them on top of the platinum-based amorphous alloy sheet, and perform hot pressing in a vacuum environment at a temperature of 205°C, a vacuum degree of 10 Pa, and a hot pressing pressure of 20 kN to obtain a platinum-based amorphous alloy sheet with barium titanate particles on the surface.

[0067] S3, immersing the platinum-based amorphous alloy sheet with barium titanate particles on the surface in an 8 mol / L hydrochloric acid solution for 10 h to completely dissolve the barium titanate particles embedded in the platinum-based amorphous alloy sheet to obtain a platinum-based amorphous alloy substrate with a nanoscale porous structure;

[0068] S4. Placing a platinum-based amorphous alloy substrate with a nano-scale porous structure in a three-electrode system for electrodeposition, wherein the working electrode is a platinum-based amorphous alloy substrate with a nano-scale porous structure, the counter electrode is a platinum sheet, the reference electrode is a silver chloride electrode, the electrolyte is a ruthenium chloride-potassium chloride mixture, the concentration of ruthenium chloride in the ruthenium chloride-potassium chloride mixture is 0.5 mmol / L, the concentration of potassium chloride in the ruthenium chloride-potassium chloride mixture is 0.15 mol / L, the electrodeposition voltage is -0.356 V (relative to the voltage of a standard hydrogen electrode), and the electrodeposition time is 800 s, to obtain a platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface;

[0069] S5. The platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface is subjected to heat treatment at a temperature of 450° C. for a heat treatment time of 150 min to obtain a platinum-based amorphous alloy porous catalyst with nano-scale ruthenium oxide loaded on the surface.

[0070] Comparative Example

[0071] The catalyst in this comparative example is commercial common ruthenium oxide, and the catalytic effect of chlorine evolution reaction is tested using common ruthenium oxide catalyst. The specific operation is as follows:

[0072] Drip coating RuO2 (ruthenium oxide) electrode: The prepared drip coating slurry includes the following raw materials: commercial ruthenium oxide with a particle size of 200-300nm, ultrapure water, anhydrous ethanol, and Nafion (perfluorosulfonate polymer). The concentrations of each raw material in the slurry are 5 mg / mL of ruthenium oxide, 700 uL / mL of ultrapure water, 280 μl / mL of anhydrous ethanol, and 20 μL / mL of 5% Nafion aqueous solution (perfluorosulfonate polymer). Before drip coating, the slurry was treated in ultrasonic cleaning for 30 minutes to make it evenly dispersed, and then 30 μL was taken three times and dripped on a glassy carbon electrode with a diameter of 5 mm. After drying, the desired drip coating electrode was obtained. The performance of the chlorine evolution reaction of the drop-coated electrode was tested using the Chenhua CHI660 electrochemical workstation three-electrode system. The drop-coated electrode was the working electrode, the platinum electrode was the counter electrode, the silver / silver chloride electrode was the reference electrode, and the electrolyte was 3 mol / L sodium chloride solution. The efficiency was tested using the chronoamperometry method. The voltage-efficiency-time graph is shown in the figure. Figure 8 As shown in the curve, the current density is 30mA / cm -2 , its catalytic efficiency for chlorine evolution reaction is only 44.8%.

[0073] The platinum-based amorphous alloy porous catalyst with surface-loaded nano-level ruthenium oxide of Example 3 of the present invention was tested for the catalytic effect of chlorine evolution reaction. The operation is as follows: take a platinum-based amorphous alloy porous catalyst sample with surface-loaded nano-level ruthenium oxide of 5 mm in diameter, and use silver colloid to stick the catalyst sample to a glassy carbon electrode with a diameter of 5 mm. After the silver colloid solidifies, a working electrode of a platinum-based amorphous alloy porous catalyst with surface-loaded nano-level ruthenium oxide is formed. Using a standard three-electrode system, a silver-silver chloride electrode is used as a reference electrode, a platinum sheet electrode is used as a counter electrode, and a glassy carbon electrode with a platinum-based amorphous alloy porous catalyst with surface-loaded nano-level ruthenium oxide is used as a working electrode. The electrolyte is 3 mol / L sodium chloride solution, and the test is performed using Chenhua CHI660 electrochemical workstation. The calculation formula for the concentration of theoretical chlorine production is: In the formula, Q is the amount of charge generated; L is the volume of the electrolyte; F is the Faraday constant. The actual chlorine concentration generated is tested using the Hach chlorine measuring equipment.

[0074] like Figure 5 As shown in the figure, it is a voltage-efficiency diagram of the chlorine evolution reaction, and the efficiency test time corresponding to each voltage is 150s. It can be seen from the figure that with the increase of voltage, the chlorine production efficiency shows an upward trend, which shows that the platinum-based amorphous alloy porous catalyst with surface-loaded nano-scale ruthenium oxide has a good catalytic effect on the chlorine evolution reaction, and with the increase of voltage, the efficiency of chlorine production continues to increase. It can be understood that the porous structure on the platinum-based amorphous alloy can greatly increase the specific surface area and realize more active sites to improve the efficiency of the chlorine evolution reaction; at the same time, the electrodeposited ruthenium oxide is nano-level, with high catalytic efficiency and stable performance, which improves the reaction efficiency of the chlorine evolution reaction and increases the amount of chlorine generated.

[0075] The surface-loaded nano-sized ruthenium oxide-containing platinum-based amorphous alloy porous catalyst of Example 3 of the present invention was subjected to linear potential scanning (linear sweep voltammetry, LSV) in 3 mol / L sodium chloride solution and 3 mol / L sodium nitrate solution, respectively. The LSV curve is shown in FIG. Figure 6 As shown, since sodium nitrate contains only nitrate, it is used to replace the occurrence of oxygen evolution reaction. Figure 6 It can be seen from the curve in that the potential of chlorine evolution reaction is much earlier than that of oxygen evolution reaction, and the current density is 10 mA / cm 2 When the voltage is 1.4-1.6V, the overpotential is only 97 mV. When the voltage is 1.4-1.6V, the chlorine evolution reaction is much more than the oxygen evolution reaction, which further illustrates that the catalyst of the present invention has excellent catalytic effect, and the chlorine evolution reaction can occur at a very low voltage, thereby saving energy. Figure 7 As shown in the figure, it is a voltage-efficiency-time diagram of the chlorine evolution reaction. From the curve in the figure, it can be seen that during the 200-hour catalytic chlorine evolution reaction, the catalytic efficiency of the platinum-based amorphous alloy porous catalyst can be stably maintained at about 65%, with high catalytic efficiency and long-term effectiveness; when the current density is 30 mA / cm 2 It can be seen from the voltage-time graph that the voltage has no obvious increase or fluctuation within 200 hours, which proves that the platinum-based amorphous alloy nanoporous catalyst prepared by the present invention is not only highly efficient but also has super long stability in the application of catalytic chlorine evolution.

[0076] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction, characterized in that: The following steps are involved: S1, platinum, nickel, copper and phosphorus are mixed in proportion, smelted and suction cast, and cut to obtain platinum-based amorphous alloy sheets. The obtained platinum-based amorphous alloy sheets are Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 ; S2, placing nano-scale barium titanate particles with a particle size of 30-200 nm on the platinum-based amorphous alloy sheet, and hot pressing under vacuum environment and hot pressing temperature conditions of 190-205° C. to embed the nano-scale barium titanate particles into the surface of the platinum-based amorphous alloy sheet, thereby obtaining a platinum-based amorphous alloy sheet with barium titanate particles on the surface; S3, immersing the platinum-based amorphous alloy sheet with barium titanate particles on the surface in an acidic solution, wherein the acidic solution is a 4-8 mol / L hydrochloric acid solution, and the reaction immersion time is 10-12 h, so as to dissolve the barium titanate particles embedded in the platinum-based amorphous alloy sheet and obtain a platinum-based amorphous alloy substrate with a nano-scale porous structure; S4, electroplating a platinum-based amorphous alloy substrate having a nano-scale porous structure, wherein the electroplating electrolyte is a ruthenium chloride-potassium chloride mixed solution, to obtain a platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface; S5. Heat-treating the platinum-based amorphous alloy porous substrate with nano-scale ruthenium loaded on the surface to obtain a platinum-based amorphous alloy porous catalyst with nano-scale ruthenium oxide loaded on the surface.

2. The method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction according to claim 1, characterized in that: In step S1, the mass ratio of platinum, nickel, copper and phosphorus is 36:1:3:

2.

3. The method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction according to claim 2, characterized in that: In step S1, a platinum-based amorphous alloy rod is obtained after suction casting, and is cut into platinum-based amorphous alloy discs. The platinum-based amorphous alloy discs have a thickness of 750-800 μm and a diameter of 2-5 mm.

4. The method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction according to claim 1, characterized in that: In step S2, the vacuum degree of the vacuum environment is 5-10 Pa, and the hot pressing pressure is 15-20 kN.

5. The method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction according to claim 1, characterized in that: In step S4, the electrode system of the electrodeposition is a three-electrode system, the working electrode is a platinum-based amorphous alloy substrate with a nanoscale porous structure, the counter electrode is a platinum sheet, and the reference electrode is a silver chloride electrode. The electrodeposition voltage is -0.356 V relative to the standard hydrogen electrode, and the electrodeposition time is 500-800 s.

6. The method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction according to claim 1, characterized in that: In step S4, the concentration of ruthenium chloride in the ruthenium chloride-potassium chloride mixed solution is 0.1-0.5 mmol / L, and the concentration of potassium chloride in the ruthenium chloride-potassium chloride mixed solution is 0.05-0.15 mol / L.

7. The method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction according to claim 1, characterized in that: In step S5, the heat treatment temperature is 420-450°C, and the heat treatment time is 150-180 min.

8. The method for preparing a platinum-based amorphous alloy porous catalyst for chlorine evolution reaction according to claim 1, characterized in that: The particle size of the surface-supported ruthenium oxide is 140-400 nm.

9. A platinum-based amorphous alloy porous catalyst for chlorine evolution reaction, obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The invention comprises a platinum-based amorphous alloy substrate having a nano-scale porous structure and nano-scale ruthenium oxide loaded on the surface of the platinum-based amorphous alloy substrate, wherein the platinum-based amorphous alloy substrate is Pt 57.5 Cu 14.7 Ni 5.3 P 22.5 The pore size of the porous structure of the platinum-based amorphous alloy substrate is 30-200 nm, and the particle size of the nano-scale ruthenium oxide is 140-400 nm.